ANALISIS INDUSTRI BUDAYA PADA DESAIN PRODUK KEMASAN MAKANAN INDUSTRI KECIL MENENGAH (1KM) - Hidayat, Moch. Junaidi (Acintya, 2009)
Discussing about packaging is always interesting especially discussing topic of food packaging which grows quite fast at this time. Packaging, at this moment, is not only comprehended as a container~ apackage, orfood protector but also comprehended as a business strategy, sign jfi cation process and an understanding about difference principle of social values and packaging tradition itself. Here is the cultural industry especially an understanding of the consumptive society and packaging becomes one of the interesting objects to talk about. This article tries to describe the meaning of object as a sign through the study ofproduct semantics and the understanding ofpackaging as a critic towards industrial culture and creativity by taking food packaging that is produced by small industry. The object of this research is food packaging offruit chips ‘Nature’ in small industry, Batu, Malang. Keywords : Food Packaging, Culture Industry, Product Semantic